Draft Annual Plan (2011-12) [Statements] Government of Puducherry - Planning Commission (Planning Commission, 2011)
Proposed Outlays - Major Heads / Minor Heads Of Development, Proposed Outlays -Major Heads / Minor Heads Of Development : From State Budget, State PSE’S And Local Bodies, Proposed Outlays - Major Heads / Minor Heads Of Development - For Rural And Urban Local Bodies, Proposed Outlay On Continuing And New Schemes, Physical Targets And Achievements, Statement Regarding Externally Aided Projects, Bharat Nirman Programmes, Centrally Sponsored Schemes, Tribal Sub Plan (TSP): Financial Outlays, Tribal Sub Plan (TSP) : Physical Targets And Achievements.
Government of Puducherry Planning and Research Department Union Territory of Puducherry